2012
DOI: 10.1007/s11427-012-4418-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathways related to mitochondrial dysfunction in cartilage of endemic osteoarthritis patients in China

Abstract: In this paper, we present the first evidence of differences in the mitochondria-related gene expression profiles of adult articular cartilage derived from patients with Kashin-Beck disease and normal controls. The expression of 705 mitochondria-related genes was analyzed by mitochondria-related gene expression analysis and ingenuity pathways analysis. Mitochondria-related gene expression analysis identified 9 up-regulated genes in Kashin-Beck disease based on their average expression ratio. Three canonical pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…It was indicated that the dysfunction of the mitochondria play an important role in KBD chondrocyte damages in our recent study, and T-2 toxin, a possible pathogenic factor of KBD, increases Bax protein production and induces chondrocyte apoptosis [19] , [20] , [23] , [24] . The present data from analyses of cell viability, mitochondrial function and mitochondria- mediated apoptosis reveal that T-2 toxin caused insults to human chondrocytes via a mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that the dysfunction of the mitochondria play an important role in KBD chondrocyte damages in our recent study, and T-2 toxin, a possible pathogenic factor of KBD, increases Bax protein production and induces chondrocyte apoptosis [19] , [20] , [23] , [24] . The present data from analyses of cell viability, mitochondrial function and mitochondria- mediated apoptosis reveal that T-2 toxin caused insults to human chondrocytes via a mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reported that expressions of certain genes related to the function of mitochondria were altered in RA patients. Notably, the relevant genes, which include the ATP6, SCO2 , CYTB, DN1, COX1, ANT1 , are mainly function in oxidative phosphorylation, whereas dysfunction in oxidative phosphorylation related genes is closely related to the systemic juvenile idiopathic arthritis and endemic osteoarthritis [40], [41]. This largely indicates that both RA and OA can be classified as mitochondrial disorder.…”
Section: Discussionmentioning
confidence: 99%
“…applied to analyze the gene expression profile data of the KBD cartilage vs the healthy cartilage. This analysis found that the apoptosis-, hypoxia-and mitochondria-related pathways were significantly up-regulated in the KBD patients compared to the healthy controls 58,59 . For instance, the pathways related to various types of the intracellular stress, including the growth factor withdrawal, the DNA damage, the unfolding stresses in the endoplasmic reticulum, and the death receptor stimulation were affected by the disease, in addition to the adaptive immunity-associated gene expressions in the peripheral blood mononuclear cells 60 .…”
Section: The Gene Expression Profilingmentioning
confidence: 91%